TAPPING INTO ENGAGEMENT: THE ROLE OF CONTENT STRATEGIES IN BOOSTING LOYALTY AND WORD-OF-MOUTH FOR E-WALLETS - Alya Hadijah Stephanie; Rifelly Dewi Astuti (Jurnal Apresiasi Ekonomi, 2025)
The development of digital payment systems in Indonesia has significantly accelerated the adoption of digital wallets, with GoPay emerging as one of the leading players. Amid intense competition, social media content strategy has become crucial in driving consumer engagement, which subsequently influences word-of-mouth (WOM) and customer loyalty. This study aims to examine the effects of content appeal (infotainment, relational, and remunerative), content vividness, and content interactivity on WOM and customer loyalty, with consumer engagement serving as a mediating variable. A quantitative approach was employed through a survey of 230 active GoPay users who follow the official Instagram account @GoPayIndonesia and had interacted with its content in the past three months. The data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM). The results reveal that six out of seven proposed hypotheses are statistically significant. Infotainment content, remunerative content, content vividness, and content interactivity all positively influence consumer engagement. Among these, content vividness exerts the strongest effect on engagement. Conversely, relational content was not statistically significant, although it was descriptively appreciated by respondents. Furthermore, consumer engagement was found to be a significant mediator in the relationship between content characteristics and both WOM and customer loyalty. This research contributes empirical insights to the field of digital marketing literature and offers strategic recommendations for digital wallet brands to enhance the effectiveness of their social media content strategies.